1996
DOI: 10.1093/oxfordjournals.aje.a008902
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia following Occupational Exposure to 60-Hz Electric and Magnetic Fields among Ontario Electric Utility Workers

Abstract: In a nested case-control study of 1,484 cancer cases and 2,179 matched controls from a cohort of 31,543 Ontario Hydro male employees, the authors evaluated associations of cancer risk with electric field exposure and reevaluated the previously reported findings for magnetic fields. Pensioners were followed from January 1, 1970, and active workers (including those who left the corporation) from January 1, 1973, with both groups followed through December 31, 1988. Exposures to electric and magnetic fields and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 32 publications
4
64
1
2
Order By: Relevance
“…Employment in "electrical occupations" has repeatedly been associated with increased risk (20), whereas studies based on quantitative exposure estimates have produced negative or equivocal results (21)(22)(23)(24). In the present study the absence of an association with magnetic field exposure in the production cohort was contrasted by a statistically significant, positive association with employment as a maintenance electrician.…”
Section: Cancers Of the Brain And Lymphatic And Hematopoietic Tissuecontrasting
confidence: 66%
“…Employment in "electrical occupations" has repeatedly been associated with increased risk (20), whereas studies based on quantitative exposure estimates have produced negative or equivocal results (21)(22)(23)(24). In the present study the absence of an association with magnetic field exposure in the production cohort was contrasted by a statistically significant, positive association with employment as a maintenance electrician.…”
Section: Cancers Of the Brain And Lymphatic And Hematopoietic Tissuecontrasting
confidence: 66%
“…Occupational exposure to electromagnetic fields was not significantly associated with risk of NHL in some studies, [358][359][360] although an inverse association was reported among workers with high-intensity exposure in one study. 170 Neither the latter study nor one other provided evidence of a doseresponse relationship between NHL risk and increasing electromagnetic radiation exposure, based on intensity of potential exposure and cumulative exposure level.…”
Section: Radiation Exposurementioning
confidence: 88%
“…170 Neither the latter study nor one other provided evidence of a doseresponse relationship between NHL risk and increasing electromagnetic radiation exposure, based on intensity of potential exposure and cumulative exposure level. 170,358 In a Canadian study of electric utility workers, the authors evaluated the risk of NHL based on percentage of time above a specified threshold of electric field and magnetic field exposure. 361 Significant positive associations were found for the upper tertile of percentage of time spent above electric field intensities of 10 (OR 5 3.05, 95% CI: 1.07-8.80) and 40 (OR 5 3.57, 95% CI: 1.30-9.80) Volts per meter, but the strength of association diminished and was no longer significant among higher intensity categories.…”
Section: Radiation Exposurementioning
confidence: 99%
“…[1][2][3][4][5] This may be particularly the case for industrial high exposure to electric and/or magnetic fields, derived not only from 50 or 60 Hz power frequency sources, but also from high-frequency transmitters. 6,7) Equivocal evidence of increased risk of brain tumors and leukemia development has been presented. [8][9][10][11][12][13] The use of portable cellular phones is rapidly expanding in many countries, and the potential health hazards to humans of the electromagnetic waves that they use is therefore of great concern.…”
mentioning
confidence: 99%